2021
DOI: 10.1155/2021/9972968
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] A New Survival Model Based on Cholesterol Biosynthesis‐Related Genes for Prognostic Prediction in Clear Cell Renal Cell Carcinoma

Abstract: In our study, the value of cholesterol biosynthesis is related to clinical analysis in 32 cancer forms in the GSEA database facility. We have a mutation between 25 CBRGs. In The Cancer Genome Atlas database, clear cell renal cell carcinoma (ccRCC, n = 539 ) was upregulated or downregulated in 22 out of 25 cases ( n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 34 publications
1
8
0
Order By: Relevance
“…In particular, HIF expression drives lipid deposition in ccRCC via the repression of fatty acid metabolism (Du et al, 2017). Importantly, it was previously shown that low expression of FDPS, FDFT1, HMGCS1, HMGCR and IDI1 genes and high expression of SQLE were associated with patients with high-risk of ccRCC (Qi et al, 2021). Thus, by up-regulating 5 out of 6 genes in this prognostic signature, AB668 could represent a therapeutic option to counteract ccRCC tumor progression.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, HIF expression drives lipid deposition in ccRCC via the repression of fatty acid metabolism (Du et al, 2017). Importantly, it was previously shown that low expression of FDPS, FDFT1, HMGCS1, HMGCR and IDI1 genes and high expression of SQLE were associated with patients with high-risk of ccRCC (Qi et al, 2021). Thus, by up-regulating 5 out of 6 genes in this prognostic signature, AB668 could represent a therapeutic option to counteract ccRCC tumor progression.…”
Section: Resultsmentioning
confidence: 99%
“…AB668 activated p38MAPK, a tumor suppressor well known for its role in transducing stress signals from the environment (Figure 3a). Interestingly, mouse modeling studies showed that mTOR activation in combination with inactivation of the p38MAPK initiates renal cell carcinoma (Wu et al, 2021).…”
Section: Target Engagement Of Ab668 In Cancer and Healthy Cellsmentioning
confidence: 99%
“…In addition, in the past few decades, the construction of risk models around cancer-related biological processes or signaling pathway-related genes has succeeded [ 41 43 ]. Therefore, inspired by previous research, we used angiogenesis-related genes to construct a risk model for BRCA.…”
Section: Discussionmentioning
confidence: 99%
“…Its development often involves biological pathways and multiple gene clusters with specific functions. Therefore, current scientific research is increasingly observing cancer progress at the level of biological pathways [ 49 51 ].…”
Section: Discussionmentioning
confidence: 99%